Ethanolic Extracts of Young Papaya Seed (Carica papaya, Linn) Decrease Spermatocytes, Leydig Cells, and Androgen Receptor of Leydig Cells of Adult Mice (Mus musculus) - Christopher Ryalino (Journal of Global Pharma Technology, 2016)
Background: Uncontrolled population growth is one of the problems in Indonesia. Among the various types of wild plants that can be used as anti-fertility drugs are papaya plants. This study aims to determine the effect of extracts on the number of spermatozoa, Leydig cells and androgen receptor (AR) expression on Leydig cells as an anti-fertility mechanism. Materials and Methods: This was an experimental, randomized posttest-only controlled group study. We used a total of 36 Wistar rats as the subjects of this study. The rats were classified equally into two groups by simple random sampling method. Group E rats received 0.5 mL ethanol extract of papaya seeds for 50 days (orally), and the rats in Group C (control) received 0.5 cc aquabidest for 50 days. Results: The treatment group showed a decrease in the number of spermatozoa (201.86 vs. 94.3, p <0.001), a decrease in the number of Leydig cells (7.61 vs. 3.32, p <0.001), and decreased AR expression of Leydig cells (46.19 vs. 18.48, p <0.001) compared to the control group. Conclusion: ethanol extracts of young papaya seeds significantly reduce the number of spermatocytes, Leydig cells, and the AR expression of the Leydig cells.Keywords: Young papaya seed, Male anti-fertility, Androgen receptor, Leydig cells.